2006
DOI: 10.1152/ajprenal.00281.2005
|View full text |Cite
|
Sign up to set email alerts
|

An emerging role for calcineurin Aα in the development and function of the kidney

Abstract: For many years, calcineurin has been a familiar molecule as a target of the immunosuppressive agents cyclosporin A and FK-506. Calcineurin inhibition interferes with T cell signaling by preventing activation of the transcription factor NFATc. However, calcineurin is expressed in most tissues in the body, and calcineurin inhibition undoubtedly alters many other cellular processes. As a result, serious side effects of calcineurin inhibitors regularly occur, including hypertension and renal dysfunction. Because n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
(47 reference statements)
5
34
0
Order By: Relevance
“…Another research found that there is only a small amount of CaN expression in a normal kidney, mainly in renal proximal tubules. 18 Gooch et al 19,20 reported that CaN expression in kidney tissue increased, and the activity of CaN phosphatase also upregulated in the early stage of diabetes. CaN played an important role in glomerulosclerosis of DN, and inhibiting CaN could obviously alleviate the degree of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another research found that there is only a small amount of CaN expression in a normal kidney, mainly in renal proximal tubules. 18 Gooch et al 19,20 reported that CaN expression in kidney tissue increased, and the activity of CaN phosphatase also upregulated in the early stage of diabetes. CaN played an important role in glomerulosclerosis of DN, and inhibiting CaN could obviously alleviate the degree of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…9 The CaN/ NFATc pathway was thought to play an important role in TGF-b-mediated induction of glomerular hypertrophy and FN expression, which is in agreement with other literature reporting that administration of CaN inhibitor CsA blocked accumulation of both CaN protein and CaN activity and substantially reduced ECM accumulation and hypertrophy in diabetic glomeruli. 10,11 We have found that NCTD can alleviate the expression of CaN in tubules in DN. 6 However, CaN is primarily expressed in the epithelium of proximal tubules.…”
Section: Effects Of Can Sirna On Can Mrna and Protein Expression Of Hmentioning
confidence: 93%
“…In other words, increased protein levels may be a reliable indicator of phosphatase activity. 11,13 Therefore, we only examined the expression of CaN protein in HK-2 cells. According to our study, we found that NCTD treatment inhibited the increased CaN expression in HK-2 Then, our experiments were performed using CaN targeting siRNA (a targeting catalytic subunit of CaN Aa isoform) to knock down CaN in mRNA and protein levels.…”
Section: Effects Of Can Sirna On Can Mrna and Protein Expression Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin, a ubiquitously expressed calcium-/calmodulin-dependent serine-threonine phosphatase, has been shown to play a role in the context of TAL function. [6][7][8][9][10][11] Calcineurin inhibitors are widely used as immunosuppressive drugs and have undisputed benefits in decreasing rejection rates after transplantation, but also have major side effects including hypertension. Their systemic effects on the sympathetic nervous system or the renin-angiotensin-aldosterone axis have been described, but much less information is known about the cellular mechanisms of calcineurin-dependent regulation of renal transporters.…”
mentioning
confidence: 99%